Exploring the Role of Acupressure in Blood Pressure Reduction: A Community-Based Study in RT 15 Pekauman - Anthasyari, Aufar; Rachman, Aulia; Agustina, Heny; Fikri, Muhammad; Jannah, Rizky Miftahul; Yulistia Dewi (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
In Pekauman Village, South Banjarmasin, hypertension is the most common non-communicable disease, often undetected due to the absence of obvious symptoms. Problem Solving for Better Health (pendekatan sederhana namun efektif untuk mengatasi tantangan kesehatan) activities were carried out, including education, blood pressure checks, and acupressure therapy. Headaches in hypertension can lead to disrupted brain circulation and risk of stroke. Acupressure, a non-pharmacological therapy, helps lower blood pressure and relieve headaches by stimulating vasodilation through histamine release. Community development in RT 15 resulted in increased public knowledge and skill in using acupressure as a complementary method to manage hypertension.